Evaluating the Impact of an Educational Intervention Using Project-Based Learning on Postpandemic Recovery in Rural Colombia - Mercedes Carmen Arrieta-Cohen; Luz Angela Torres-Arizal; Ricardo León Gómez-Yepes (Education Sciences)
This study evaluates the impact of a Project-Based Learning (PBL) intervention on postpandemic educational recovery in rural Colombia, focusing on student competencies in mathematics, language, science, and 21st-century skills. Conducted in rural schools, the intervention aimed to address significant learning gaps exacerbated by the COVID-19 pandemic by providing teacher training and direct student support. A pretest–posttest single-group design was used to assess the effectiveness of the intervention, with standardized tests measuring academic competencies and an analytical rubric evaluating 21st-century skills. The results indicate significant improvements in math, language, and science test scores, with notable gains in problem-solving, collaborative work, communication, and critical thinking. However, a decline in creativity scores highlights the need for a stronger emphasis on fostering creativity within the PBL framework. Gender differences were observed, with female students generally outperforming males, suggesting the need for tailored instructional approaches. This study’s limitations, including the absence of a control group, nonrandom sampling, and the use of subjective assessment methods, are acknowledged, with recommendations for future research to address these issues. Despite these limitations, the findings underscore the potential of PBL to enhance student learning outcomes in rural settings, offering valuable insights for educators and policymakers aiming to support educational recovery and development in similar contexts. Further research is recommended to explore the long-term effects of PBL and to refine the intervention for broader implementation.